Analisis Dan Perbaikan Proses Bisnis Menggunakan Metode Business Process Improvement (BPI) (Studi Kasus: PT. Wonojati Wijoyo) - Tri Susanto; Djoko Pramono; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Wonojati Wijoyo is a company in industrialized furniture of teak. In this company, there are some division that was create for helping so many others short or long terms goals. Accounting and finances is the one of division in this company. There are 3 main steps or processes, the first thing is accountancy finances reports and the reports of employee's salary. The process of this business was getting some seriously problem in accounting and finances division, they always need much time to give the best report and it always exceed of the time was given. As the result, in this division also needs evaluation and repairing for better process in every aspect that what we hope and was given the best solution. The best solution is give the recommendation for the new business process and this process was believing that it was more effective. From the result of value chain analysis and decomposition of business program in reports of employee's salary. Based on evaluation of this program by using five whys analysis methods, the researcher was the main problem is in the absences still using manually program by using check log, but in this condition this manually program was susceptible of dishonest and there was some mistake in the process of recapitulation. Based on this evaluation there was done a treatment by using tools streamlining from Business Process Improvement (BPI). From the result of the recommendation this company has program for changing system of absence by using finger print and lost the old one program of recapitulation absence. From all simulation process of business it was getting a gap around 3 hours 34 minutes with 28.92% percent.